Uji Kualitas Fisik Susu Sapi Friesh Holland (Studi Kasus Peternakan Claretian Novisiat Benlutu Kabupaten TTS) - Maria M. Tefa; Stefanus Sio; Theresia Ika Purwantiningsih (JAS, 2019)
This study aims to determine the quality of milk in the Claretian Novisiat Benlutu Ranch, in terms of alcohol test, boiling test, specific gravity test and acidity degree. This study uses fresh milk samples taken at Benlutu. Alcohol test data, boiling test specific gravity test and the degree of acidity were analyzed using descriptive analysis. The data obtained were analyzed using descriptive analysis and presented in tabular form and the discussion was carried out descriptively based on average counts and standard deviations then compared with SNI 3141.1.2011 concerning the quality of fresh milk. The results of the study were negative in the alcohol test and boiling test, this is in accordance with SNI 2011 on fresh milk. Whereas the milk acidity test shows 6.8 according to SNI 2011 about milk acidity which ranges from 6.0 to 7.5, the specific gravity test shows a scale of 1.0276, this complies with SNI. Based on the results of the study it can be concluded that the fresh milk obtained from the Claretian Novisiat Benlutu Farm is physically good quality and fit for consumption, evidenced by the quality test on fresh milk fulfilling SNI in terms of alcohol test, acidity titration, and boiling test, and specific gravity test.